Development of a load monitoring system for residential purposes - Ng, Yen Ju (2017)
As the technology is advancing, more and more non-electronic devices have transformed into electronic devices such as telephone, cooking appliances, etc. As such, the global electricity consumption increases yearly and results in a bunch of environmental issues lately. This gives rise to the idea of reducing the end-user electricity consumption, which is known as Demand Side Management (DSM). Non-intrusive Load Monitoring (NILM) is solution for DSM that captures the daily household electricity usage and presents it to users. The main objective is to give the users an idea of their electricity consumption pattern, thereafter encourages them to cut-off unnecessary electricity usage. This project focuses on the design of NILM system using hardware and software approach. On the hardware side, the electricity measurement is carried out at the loads’ input end by using a power meter. Bluetooth wireless connection is used to transfer the data from the power meter to the PC. On the software side, LabVIEW and MATLAB are used to code the NILM algorithm. The data from the power meter are then analyzed by using the steady-state disaggregation method. The aim is to identify the load pattern and the respective individual load power consumption. Finally, a Graphical User Interface (GUI) is developed to display all the data to the users in a real-time basis. With the encouraging results obtained from this project, NILM would be useful to users by allowing them to monitor daily electricity consumption, thereafter reduce their electricity usage.